(untitled) (Progress Annals: Journal of Progressive Research, 2025)
The article examines modern approaches to the utilization of construction waste based on global experience. The main methods of recycling construction and demolition waste, as well as the specific features of stationary and mobile processing equipment, are analysed. Particular attention is paid to the classification of recycled fractions and their application in the production of building materials and road construction. It is shown that the recycling of construction waste reduces environmental pressure, decreases landfill volumes, and ensures the efficient reuse of secondary mineral resources. The prospects for implementing international experience in the utilization of construction waste under the conditions of Uzbekistan are also discussed.